2018
DOI: 10.1016/j.jdmm.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of history and identity discourses in cross-border tourism destination development: A Vogtland case study

Abstract: Cross-border tourism governance processes have remained complex despite increasing permeability of European borders in the last decades. While it has been suggested that the presence of cross-border socio-cultural connections may alleviate border-related tourism management complexities, no detailed studies have been conducted yet to explore this assumption. This paper analyses the role of socio-cultural relations and history and identity discourses in destination development of the cross-border Vogtland region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
(65 reference statements)
0
24
0
Order By: Relevance
“…Development potentials of sport-event tourism are indicators for tourism stakeholders (Devine & Devine, 2011;Getz & Page, 2016), which should intensify their focus on promoting and strengthening the promotion of "Drinska regatta" as sport-event of regional and interregional importance. Thus, the benefits of developing and implementing the sport-event tourism are numerous (Arnegger & Herz, 2016) and they should not be neglected within the researched region. It could be concluded that education of the local community is important for the development of sport-event tourism, (Woo et al, 2015), and should be the first step, regarding the fact that for the majority of the respondents sport-event tourism is not developed appropriate.…”
Section: Contribution Of the Local Community In Sport-event Tourism Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Development potentials of sport-event tourism are indicators for tourism stakeholders (Devine & Devine, 2011;Getz & Page, 2016), which should intensify their focus on promoting and strengthening the promotion of "Drinska regatta" as sport-event of regional and interregional importance. Thus, the benefits of developing and implementing the sport-event tourism are numerous (Arnegger & Herz, 2016) and they should not be neglected within the researched region. It could be concluded that education of the local community is important for the development of sport-event tourism, (Woo et al, 2015), and should be the first step, regarding the fact that for the majority of the respondents sport-event tourism is not developed appropriate.…”
Section: Contribution Of the Local Community In Sport-event Tourism Developmentmentioning
confidence: 99%
“…W. Ritchie et al, 2009; Weaver & Lawton, 2013), and the participation of the local population in enriching the tourism content in accordance with demands of the modern tourists. Numerous authors (Blasco et al, 2014b; Gelbman & Timothy, 2011; Jimber del Río et al, 2017; Stoffelen & Vanneste, 2018; Studzieniecki et al, 2016; Weidenfeld, 2013) indicated potentials, perspectives, and guidelines for further realization of sport-event tourism within the cross-border municipalities, including the benefits that the local community and domicile population might achieve of further development of sport-events.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of municipal mergers, actors mobilise and select different scales, development discourses and institutional structures to give coherence and legitimacy to their political opinions and practices concerning the territorial 'base unit' of regional development and planning, be it the municipality, the planned merged of a municipality, a cross-border region or something else. It is noteworthy, however, that actors may select a certain scale and development discourse, such as CBC, and adapt its related lexicon and rhetoric in pursuing and funding their own local interests and strategies which may not in themselves be so directly related to the wider policy objectives of the European Union, such as European economic integration or transnationalisation (Johnson 2009;Luukkonen 2011;Prokkola et al 2015;Stoffelen & Vanneste 2017). Thus, as Gonzales (2006, 853) aptly points out, "the language and rhetoric are not mere accessories"; through discursive strategies actors are normalising the space of regional development to make their political decisions seem as selfexplanatory as possible (Gonzales 2006).…”
Section: Theoretical Insights: the Selectivity Of Development Strategmentioning
confidence: 99%
“…Actors in Tornio see CBC as a better development strategy for improving regional competitiveness, which in this case means attracting investors, visitors, publicity, etc., rather than co-operation or amalgamation with other regional municipalities. Mobilisation of regional history and identity has become an important means in improving regional attractiveness (Paasi 2013;Stoffelen & Vanneste 2017). The narrative on the identity of the Torne River Valley has become an important part of marketing and development rhetoric (Jakola 2016).…”
Section: The Eu's Locally Contested Cbc Discoursementioning
confidence: 99%